Luteolin as an adjuvant effectively enhanced the efficacy of adoptive tumor-specific CTLs therapy - Zhiheng Lai; Yanyang Pang; Yujing Zhou; Leiyuan Chen; Kai Zheng; Shiguo Yuan; Wu Wang (BMC Cancer)
Abstract Background Luteolin, a natural flavonoid compound, has demonstrated anti-inflammatory, antioxidant, and broad anti-tumor properties. Recent studies suggest that its anti-tumor effects are linked to enhanced CTL function—including proliferation, survival, and cytotoxicity-via inhibition of the YAP/Wnt signaling pathway in tumor cells. Consequently, luteolin has potential as an adjuvant in combination therapies with adoptive immunotherapy. Methods This study first assessed luteolin’s tumor-inhibitory effects in vitro and in vivo using cytotoxicity assays, Transwell invasion tests, wound healing assays, and analyses of post-treatment tumor growth and survival time. Additionally, we explored whether luteolin combined with a DC/tumor fusion vaccine could synergistically enhance overall antitumor efficacy by boosting activation, proliferation, cytokines secretion, and cytotoxicity of effector T cells. Results Our findings indicate that luteolin, as a standalone agent, can inhibit the proliferation and invasion of colon and lung cancer cells both in vitro and in vivo to a certain extent. When combined with activated CTLs, it upregulated the expression of CD25 and CD69 in effector cells and resulted in higher levels of IL-2, TNF-α, and IFN-γ secretion in vitro. In vivo, this combination significantly curtailed subcutaneous tumor growth and extended the mean survival time of tumor-bearing mice (HCT116, A549), outperforming luteolin monotherapy. Furthermore, the efficacy of this combination therapy may be attributable to enhanced apoptosis in tumor cells, reduced proliferation, and decreased YAP expression. Conclusion The combination of luteolin and DC/tumor fusion vaccine-activated CTLs presents a novel approach for cancer treatment. As an adjuvant, luteolin downregulates YAP expression in tumor cells, enhancing CTL proliferation, cytotoxicity, and survival, thus improving tumor recognition and selective targeting. This strategy is promising for safe and effective tumor treatment.